Tracking Fluid Flow in Shallow Crustal Fault Zones: 1. Insights From Single‐Hole Permeability Estimates. Issue 4 (18th April 2020) - Brixel, B.; Klepikova, M.; Jalali, M. R.; Lei, Q.; Roques, C.; Kriestch, H.; Loew, S.
Abstract: New in situ measurements to constrain the range, distribution, and spatial (meter‐scale) variations of permeability in shallow crustal fault zones are reported based on systematic downhole tests at 0.5‐km depth in crystalline rock. Single and cross‐hole hydraulic packer tests were performed at a new dedicated test facility hosted in the Grimsel Test Site, in the Swiss Alps, following the technical instrumentation and isolation of discrete fault zones accessed by an array of boreholes. Single‐hole test results are presented in this paper, while cross‐hole experiments are reported in the companion paper. Our results reveal a sharp spatial falloff in permeability, from 10 ‐13 to 10 ‐21 m 2, with off‐fault distances of 1–5 m and characterized by a power‐law relation with fracture density. Fractures linking subparallel faults were detected as high‐permeability discrete spots several meters away from off‐fault damage. Due to the narrow (centimeter‐wide) thickness of fault cores, the hydraulic tests presented in this study do not characterize the permeability of fault core materials. The transmissivity of single fractures spans six orders of magnitude (10 ‐12 to 10 ‐6 m 2 /s) and is systematically higher in damage zones. In situ stresses appear to have a minor effect on natural, present‐day fracture transmissivity at the borehole scale. We suggest that the geometrical and topological properties of fracture systems instead tend to control the permeability of the shallow crustal faults studied. Key Points: We mapped permeability variations across shallow crustal fault zones through systematic downhole pressure pulse tests A sharp permeability decay up to eight orders of magnitude with off‐fault distance is observed Geometry and topology exert a dominant control on the permeability of fracture systems in shallow crustal settings